Disability index of low back pain in truck drivers - Pedroso, Amarilda Aparecida dos Santos; Reis, Amir Curcio dos; Souza, Rafael Rodrigo Silva de; Rabelo, Nayra Deise dos Anjos; Lucareli, Paulo Roberto Garcia; Blay, André Serra (ABCS Health Sciences, 2013)
Introduction: Low back pain leads the morbidity and disability in performing daily living activities. Truck drivers have high risks to developing low back pain due to postural and mechanical characteristics of the profession. Objective: To investigate the low back pain interference level in daily living activities of the truck drivers. Methods: This is a cross-sectional study that recruited 30 truck drivers, male, aged between 25 and 35 years old and more than five years of experience in this profession. Only individuals with chronic low back pain (at least three months), were instructed to answer the Oswestry disability index questionnaire, to classify the low back pain interference levels in daily activities. Results: Twenty-nine truck drivers were included (mean age 31.83±3.63 years, mean experience 8.93±2.4 years and a mean daily work 13.66±2.47 hours). Twenty-two truck drivers (75.86%) showed minimal disability (score 8.45±6.58) and seven (24.14%), moderate disability (score 27.14±6.3). Conclusion: Only 24.14% of the sample showed moderate disability, that can be interfering in the daily living activities performance of the truck drivers, such as; problems when sitting, lifting and standing up.